Macroscopic and microscopic description of low-energy collective states in Se 86,88 - Thiamova, G.; Grachev, Y.; Abolghasem, M.; Alexa, P.; Reinhard, Paul-Gerhard; Rodriguez, T. R.; Simpson, G. S. (Physical Review C - Nuclear Physics, 2018)
Algebraic collective model (ACM) calculations for the even-even selenium isotopes Se86,88 have been performed to describe collective properties of these two transitional nuclei with only two and four valence neutrons, respectively. From the perspective of the ACM the nuclei turn out to be only weakly deformed, described by a very γ-soft potential. This is confirmed by Skyrme and Gogny energy density functional calculations. Additionally, the fully microscopic symmetry conserving configuration mixing method with the Gogny interaction has been applied to the study of these isotopes. The results show the transitional character of Se86 and the relevant role of the triaxial degree of freedom in the structure of these nuclei.
CRIS-Team Scopus Importer:2021-07-19